ANALISIS HUBUNGAN BIAYA PRODUKSI TERHADAP LUAS LAHAN USAHATANI PADI SAWAH DI DESA ALUE MERBAU KECAMATAN LANGSA TIMUR - Nova Liana; Faoeza Hafiz Saragih; Kiagus M. Zain Basriwijaya; Cut Gustiana (Jurnal Inovasi Penelitian, 2022)
This study aims to analyze the relationship between production and land area for lowland rice farming in Alue Merbau Village, East Langsa District. This research was conducted in Alue Merbau Village, East Langsa District. The sampling technique used is simple random sampling technique with a total sample of 30 people. To determine the relationship between production costs and land area for lowland rice farming in Alue Merbau Village, East Langsa District, statistical analysis was used with the Pearson correlation method. Data processing is done using SPSS computer software. The results of this study indicate that the variable costs of seed, fertilizer costs, pesticide costs, and labor costs have a significant relationship with the area of ​​lowland rice farming in Alue Merbau Village, East Langsa District.